Risk factors and prevalence of child hearing disability in the city of Vila Velha, Espírito Santo, Brazil (Brazilian Journal of Health Research, 2022)
Introduction: Considered a public health problem, hearing loss in children can impair the language development process if the diagnosis and intervention do not occur early. Objectives: To identify the risk factors and the prevalence of hearing impairment in children attended in the Unified Health System Hearing Health Program of a university in Vila Velha, ES. Methods: Cross-sectional and retrospective study from August 2016 to August 2018. Based on data from medical records, an analysis of the results of hearing loss risk and risk indicators screening was performed. The research was approved by the University’s Research Ethics Committee. Results: Of the 123 children studied, a total of 61 had some type of hearing impairment, with 21.31% (n = 13) having cochlear sensorineural loss, identified by NHS, 36.06% (n = 22) had hearing loss. retrocochlear lesion identified by BERA, and 42.62% (n = 26) presented cochlear and retrocochlear sensorineural loss, that is, both in the NHS and in the BERA. A higher prevalence was observed in cases of stay in the incubator> 7 days, ototoxic medications, craniofacial malformations, premature birth, recurrent otitis media, associated syndromes, hyperbilirubinemia, but the only one that had statistical significance was “mechanical ventilation”. Conclusion: The findings demonstrated a high prevalence of hearing loss in children aged 0 to 5. Although the factor “mechanical ventilation” was the only one with significance, it is believed that the diagnosis of hearing loss has a strong relationship with the other identified risk factors in the study.
Keywords: Otolaryngology; Hearing; Hearing loss; Health Services; Child Health